Soluble and Non-Aggregated Phthalocyanines: Synthesis, Mechanistic Aspects and Their Main Building Blocks - Gobo, Nicholas R.S.; Brocksom, Timothy J.; de Oliveira, Kleber T. (Current Organic Synthesis, 2017)
Background: Since its discovery on the 1930 decade, phthalocyanines have occupied a prominent place in the textile and dye industries due to their thermal stability, low solubility and reactivity. However, over the last three decades, many different applications have been found for phthalocyanine derivatives including medicine, materials science, catalysis and energy fields. In this review, we discuss about the phthalocyanine chemistry, and the principal synthetic precursors as well. Strategies developed for obtaining soluble and nonaggregated phthalocyanine dyes are also covered, with insights on the reaction mechanisms. The main synthetic methods for the synthesis of symmetric and non-symmetric systems are presented and discussed. Objective: This review aims to present an overview on phthalocyanine chemistry and their principal synthetic precursors, covering strategies developed for obtaining soluble and non-aggregated phthalocyanine dyes with insights on the reaction mechanisms. Also, the main synthetic methods are presented, and different approaches to symmetric and non-symmetric phthalocyanine are discussed. Conclusion: Phthalocyanines are compounds with significant applications and growing interest in science. Their physical and chemical properties have been more and more elucidated. The major challenge is to make the synthetic protocols more suitable and cheaper, in order to allow studies and application on large scales.
Keywords: non-aggregation